The Role of Technology in COVID-19 Pandemic Management and Its Financial Impact. (13th September 2021) - Zhao, Jin; Ahmad, Zubair; Khosa, Saima K.; Yusuf, M.; Alamri, Osama Abdulaziz; Mohamed, Mohamed S.
Abstract : A pandemic caused by the novel coronavirus (COVID-19) is causing an unprecedented situation for the world's health services. Health, local communities, and government are adversely affected by the COVID-19 pandemic. Moreover, on January 21, 2020, the WHO Emergency Committee declared a global health emergency because of increasing numbers of COVID-19 case notifications from countries overseas. While the pandemic caused grave damage to socioeconomic phenomena and multiple global phenomena such as commodity prices, remittances, trade, tourism, significant job loss, and drastically lower wages, the pandemic has also negatively affected multiple global phenomena. The advent of technology has spurred significant changes in many aspects of our lives and improved the exchange of information, the presentation of data, and the management of medical resources through telemedicine. In this article, we present a mathematical data visualization approach for analyzing pandemic data behaviors, such as exponential growth and deviations using the data related to COVID-19 events. Furthermore, this article will include studies on the implications of the COVID-19 pandemic on finance sector.